STRATEGI PENINGKATAN PEMELIHARAAN KAPAL LOGISTIK TNI AD OLEH BENGPUSBEKANG GUNA MENDUKUNG TUGAS POKOK TNI [STRATEGY TO IMPROVE MAINTENANCE OF TNI AD LOGISTICS SHIPS BY BENGPUSBEKANG TO SUPPORT TNI'S MAIN DUTIES] - Harmawan, Dwi; Ali, Yusuf; Winarna, Agus (Al-Ihtiram: Multidisciplinary Journal of Counseling and Social Research, 2025)
This study aims to analyze the strategy for improving the maintenance of Indonesian Army logistics ships by Bengpusbekang to support the main tasks of the TNI, in the context of supporting the shift of personnel, materials, and other logistical supplies in various military operations throughout the Indonesian Army in the Indonesian territory. This study was conducted using the Qualitative Descriptive Analysis method using data collection techniques through interviews, document studies, and field observations to obtain normative data. The theory of this study uses strategy theory, maintenance management theory and the concept of the effectiveness of military logistics operations. The results show that the maintenance of Indonesian Army logistics ships is currently still reactive and not condition-based (Condition Based Maintenance), using aspects of budget availability, technical infrastructure, and human resources. The lack of integration of the maintenance information system also complicates planning and supervision. The improvement strategy developed includes maintenance digitalization, strengthening technician competencies, integration of logistics systems between units, and collaboration with the national defense industry. The strategic approach used allows for alignment between operational objectives (ends), methods of achievement (ways), and supporting resources (means) in the context of adaptive and efficient maintenance management. These findings are expected to provide policy input for the Indonesian Army leadership in developing a logistics ship maintenance system that is measurable, responsive, and supports the effectiveness of military operations on an ongoing basis.